2022
DOI: 10.1017/jns.2022.68
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and mental health of college students in Lebanon: a cross-sectional study

Abstract: The present study aimed to assess the prevalence of food insecurity (FI) among college students and explore its association with indicators of mental and psychosocial health. Data were collected using a cross-sectional online survey from college students in different universities in Lebanon during the Spring 2021 semester. FI was assessed using the validated eight-item food insecurity experience scale. The mental health of college students was assessed using validated screening tools for depression, anxiety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…For the rst time in the country's history, Lebanon has been agged for food insecurity risk by the United Nations (40), with 2.26 million people at risk. Food insecurity has also been found to be linked to poor mental health in students in Lebanon (15). Without economic and political reform in the country that can reduce nancial and food insecurity, we are unlikely to see major improvements in the population's mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the rst time in the country's history, Lebanon has been agged for food insecurity risk by the United Nations (40), with 2.26 million people at risk. Food insecurity has also been found to be linked to poor mental health in students in Lebanon (15). Without economic and political reform in the country that can reduce nancial and food insecurity, we are unlikely to see major improvements in the population's mental health.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, more than half of the population were suffering from anxiety and traumatic stress. Amongst college students, over a third of students at the American University of Beirut reported severe symptoms of depression and anxiety, and this was strongly associated with food insecurity (15).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with previous reports, food insecurity precipitated by weak finances, and the financial constraint inherent in higher education make these students prone to unhealthy lifestyle choices. Previous studies have found prevalence of food insecurity to be as high as 44% [ 21 ], 39% [ 22 ], 38 – 48% [ 23 , 24 ], respectively among students from University of California, Lebanon, and Australian universities, and therefore suggest a more global problem in the tertiary setting. Furthermore, although our cohort unanimously agreed that regular intake of balanced meals was an important preventive strategy to deal with anaemia, over two-thirds (73.5%) indicated skipping meals while on campus.…”
Section: Discussionmentioning
confidence: 99%
“…Both food insecurity and low fruit and vegetable intake were associated with depressive symptoms in a study by Wattick et al [96]. In a study of Lebanese college students, accounting for demographic and socioeconomic factors, food insecurity was linked with higher depression and anxiety scores compared with food secure peers [57]. In a recent study, Oh et al found links between food insecurity and substance use, including higher odds of binge drinking, cigarette smoking, and other illicit or prescription drug use after adjusting for demographic and employment factors [97].…”
Section: The Physical and Mental Health Toll Of Food Insecuritymentioning
confidence: 93%
“…Food insecurity in college remains high, with research from Australian universities indicating a food insecurity prevalence of 38-48% among students [55,56]. Similarly, a study of public and private college students in Lebanon indicated that food insecurity affected 39% of surveyed students [57]. As has been observed in US university students, food insecurity has been associated with poorer academic outcomes, with Malaysian students experiencing food insecurity having a lower GPA than food secure colleagues [58].…”
Section: Global Food Insecurity Among College Studentsmentioning
confidence: 98%